Ice hockey skate boot mechanics: Direct torque and contact pressure measures - Pearsall, D. J.; Paquette, Y. M.; Baig, Z.; Albrecht, J.; Turcotte, R. A. (Procedia Engineering, 2012)
Ice hockey is a sport characterized by high speeds, sharp turns and abrupt stops. Hence, the interaction of the foot and ankle within the skate boot is fundamental for optimal stability and propulsion. The purpose of this study was to quantify concurrently direct torque and foot-to-boot contact pressures throughout the foot and ankle's functional range of motion, with two skate boot models. Testing ten male hockey players in a seated position with hip and knee stabilized at 90°, ankle torques during plantar/dorsi-flexion (PF, DF) and inversion/eversion (INV, EVR) isokinetic movements (60°/s) were measures using a Biodex dynamometer with contact pressures collected with piezo-resistive sensors placed about nine foot-ankle regions. One conventional and one modified skate boot models were examined: the latter encompassing greater tendon guard and tongue flexibility. Results showed the modified skate had substantial increases in ankle range of motion (14.8°, p<0.05), particularly in the PF direction (+12.6°) versus the conventional skate, and a trend towards increased PF torque (64.2 vs. 62.7 Nm) and work per stroke (13.0 vs. 8.9 kJ). No significant differences in INV/EVR were noted. Contact pressure distribution was altered significantly BOTH at the sites adjacent to the boot construction modifications AND at remote sites, indicating an altered manner of foot leverage within the boot to create PF/DF torque, particular at PF to DF transition phases. In summary, this novel study is the first to directly ascertain the mechanical interactions of the foot and skate boot, and demonstrated this benchmarking protocol's sensitivity to functionally discriminate between boot design changes.